A compendium of participatory evaluation data on sorghum, finger millet and beans for climate change adaptation in Kenya, Uganda and Tanzania - Otieno, Gloria Atieno (2021)
The compendium contains participatory evaluation data collected from crowd sourcing varieties of finger millet, sorghum, and beans from national genebanks in Kenya, Tanzania and Uganda by over 1600 farmers over the period 2017-2019 in CCAFS climate smart villages of Hoima-Uganda, Nyando-Kenya and Hombolo and Singida in Tanzania. The compendium also contains additional Participatory Varietal Selection data collected on-station in three research stations of ARI-Hombolo, NARO-Bulindi ZARDI and Nyando in Kenya. Finally the compendium also presents organoleptic data of top performing varieties collected from farmers in Hoima Uganda.